UNCERTAINTY AND CROP PRODUCTION PLANNING IN THE CONTEXT OF SUPPLY CHAIN MANAGEMENT OPTIMIZATION - Kussaiynov, Talgat A.; Mussina, Gulnara S. (International Journal of Supply Chain Management, 2019)
Abstract- In the supply chain management system (SCM) in agribusiness, it is critical to ensure the economicsustainability of farms - suppliers of raw materials for processing. The purpose of the study was to develop methods and procedures for calculating the projected values of income per hectare from the crops cultivated, taking into account the conditions of crop production in the Northern Kazakhstan. The main features of crop production in the region are (1) it is highly exposed to the risks of natural and market properties; (2) farms are, as a rule, diversified with the cultivation of many different crops.